2016
DOI: 10.1128/iai.01211-15
|View full text |Cite
|
Sign up to set email alerts
|

The Yersiniabactin-Associated ATP Binding Cassette Proteins YbtP and YbtQ Enhance Escherichia coli Fitness during High-Titer Cystitis

Abstract: The Yersinia high-pathogenicity island (HPI) is common to multiple virulence strategies used by Escherichia coli strains associated with urinary tract infection (UTI). Among the genes in this island are ybtP and ybtQ, encoding distinctive ATP binding cassette (ABC) proteins associated with iron(III)-yersiniabactin import in Yersinia pestis. In this study, we compared the impact of ybtPQ on a model E. coli cystitis strain during in vitro culture and experimental murine infections. A ybtPQ-null mutant exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…coli siderophore-dependent growth assay. The assay was adapted from a previously published Fe(III)-Ybt-dependent growth assay, and apo-Ybt was purified as previously described (16,19). UTI89 was grown overnight in LB broth at 37°C under shaking conditions and then washed 3 times by centrifugation and resuspension in a volume of PBS equal to the culture volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…coli siderophore-dependent growth assay. The assay was adapted from a previously published Fe(III)-Ybt-dependent growth assay, and apo-Ybt was purified as previously described (16,19). UTI89 was grown overnight in LB broth at 37°C under shaking conditions and then washed 3 times by centrifugation and resuspension in a volume of PBS equal to the culture volume.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest that the early stages of ascending UTI are competitive and favor isolates with specific siderophore profiles. In this and other studies, Ybt, a siderophore encoded by the Yersinia high pathogenicity island (HPI), was associated with urinary tract virulence (7,(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the import of metal-chelated Ybt is an essential pathway for the microbes to acquire necessary metal ions. It has been established that deletion of YbtP or YbtQ gene in UPEC has no effect on the extracellular release of metal-free Ybt, but has detrimental effect on the intracellular metal uptake and later leads to profound decreased UTIs in a cystitis mouse model (11). Thus, it is suggested that the heterodimer YbtPQ is an ABC importer responsible for specific uptake of metal-chelated Ybt molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Among HPI-encoded proteins, transport-associated outer and inner membrane proteins are required for Fe(III)-Ybt dependent growth and are expressed in a YbtA-dependent manner 8 , 9 , 12 , 13 . FyuA ( f erric y ersiniabactin u ptake A, Psn in Yersinia pestis ) is an outer membrane protein with structural and functional features that are typical of TonB-dependent outer membrane siderophore transporters 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%